PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN CITA RASA TERHADAP KEPUASAN KONSUMEN PADA DURIAN KOCOK 77 TEMPULING - Miftahul Husna Hutapea; Nur Ahmadi Bi Rahmani; Khairina Tambunan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of the culinary business has resulted in a variety of unique culinary delights, one of which is Durian Shake which is popular with many groups, especially young people, causing quite long queues. Based on observations, service quality, price perception and taste are very important things for consumers, when consumers feel satisfied it will have an impact on consumer satisfaction. The purpose of this research is to determine the influence of service quality, price perception and price perception on consumer satisfaction. The object of this research is consumers of Duriankocok77 Tempuling in Medan Tembung District. This research uses a quantitative method in which to determine the sample using the solvin formula with the results being 89 consumers of Duriankocok77 Tempuling. This research uses classical assumption test data analysis techniques, descriptive and multiple linear analysis with the help of the SPSS version 26 application. The results of this research show that the factors of service quality, price perception and taste have a positive and significant effect on consumer satisfaction. And the factors of service quality, price perception and taste simultaneously influence consumer satisfaction with Duriankocok77 Tempuling.